FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN LANSIA KE POSYANDU DI DESA SEMALI SEMPOR KEBUMEN - Juni Sofiana; Umi Laelatul Qomar; Dyah Puji Astuti (Jurnal Ilmiah Kesehatan Keperawatan, 2018)
Posyandu (Integrated service center) of elderly is a center of community activities in effort to provide health services to elderly. Posyandu is intended to improve the health quality of elderly to achieve a happy and meaningful life in their family and community. Posyandu has not been maximal by used, this this is indicated by the decline of their visit. The purpose to find out the factors (age, sex, occupation, education level) that affect the elderly visit elderly to posyandu at Semali, Sempor , Kebumen. This study was conducted by using quantitative techniques, with cross sectional method. samples were taken by total sampling technique with 327 respondents. Test data analysis of this study was done by using Chi Square statistical tests. The result 1) There is no relationship between age (p = 0.229) and gender (p = 0.220) with the active visit of elderly posyandu. 2) There is a relationship between occupation (p = 0.010), and education level (p = 0.016), with the activity of the elderly to the Elderly Posyandu.The result of Statistical test shows that there is a relationship between occupation and education level towards the active visit of elderly to posyandu. Key word : elderly, posyandu, visit